Pengaruh Pendapatan Asli Daerah dan Dana Alokasi Umum Terhadap Tingkat Kemiskinan melalui Belanja Modal sebagai Variabel Intervening pada Kabupaten/Kota di Provinsi Bali - Prami Saraswati, I Gusti Agung Ayu; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 11, November 2016 (pp. 1168 - 1346), 2016)
This study aimed to determine the direct and indirect influence of the local revenue and general allocation fund against poverty with capital expenditure as an intervening variable. This research was conducted in all districts / municipalities in Bali Province. The data collection is done through the documents contained in the BPS Bali. The data used in this research is secondary data, while the analysis method used is the analysis of lane or path analysis to determine the effect, directly and Sobel test to determine the effect indirectly. The analysis showed that the local revenue and general allocation have significant positive effect on capital spending. Local revenue and general allocation have significant negative effect on poverty levels and capital expenditures have significant negative effect on poverty levels. Through capital expenditure, the local revenue and general allocation have significant indirect effect on poverty levels. The analysis show that an intervening variable capital expenditure of local revenue and general allocation fund.
Keywords: local revenue; general allocation fund; capital expenditures; the level of poverty